Effect of different salts on the development of Fusarium solani var. coeruleum, a causal agent of potato dry rot - Mecteau, Mélanie; Arul, Joseph; Tweddell, Russell (Phytoprotection, 2008)
The objectives of this study were (1) to evaluate the effect of different salts on the in vitro development of Fusarium solani var. coeruleum, and (2) to evaluate the efficacy of the salts for reducing dry rot severity caused by the pathogen in potato tubers. The study showed that several salts significantly inhibited the mycelial growth of F. solani var. coeruleum. Aluminium acetate, aluminium chloride, sodium benzoate, sodium metabisulfite, potassium sorbate and trisodium phosphate completely inhibited mycelial growth. Exposure of F. solani var. coeruleum conidia to aluminium acetate, potassium sorbate, sodium benzoate, sodium metabisulfite or trisodium phosphate at 0.2 M resulted in 100% mortality of the conidia after 1 h while aluminium chloride and aluminium lactate caused 100% mortality after an exposure of 24 h. In order to evaluate the effect of salts on potato dry rot development, F. solani var. coeruleum-inoculated tubers were treated with the different salts and disease severity was evaluated following an incubation period of 7 d. Among the test salts, only aluminium chloride caused a significant reduction in potato dry rot compared with the control. The study points out the possibility of using aluminium chloride to control potato dry rot.